Improves the In Vitro Developmental Competence and Reprogramming Efficiency of Cloned Bovine Embryos by Additional Complimentary Cytoplasm - Xu, Lianguang; Mesalam, Ayman; Lee, Kyeong-Lim; Song, Seok-Hwan; Khan, Imran; Chowdhury, M M R; Lv, Wenfa; Kong, Il-Keun (Cellular reprogramming, 2019)
Somatic cell nuclear transfer (SCNT) is a useful technology; however, its efficiency is low. In this study, we investigated the effects of cytoplasmic transfer into enucleated oocytes on the developmental competence and quality of cloned preimplantation bovine embryos via terminal deoxynucleotidyl transferase dUTP nick-end labeling, quantitative reverse transcription PCR, and immunocytochemistry. We used cytoplasm injection cloning technology (CICT), a new technique via which the cytoplasmic volume of an enucleated oocyte could be restored by injecting ∼30% of the cytoplasm of a donor oocyte. The percentages of embryos that underwent cleavage and formed a blastocyst were significantly higher (p < 0.05) in the CICT group than in the SCNT group (28.9 ± 0.8% vs. 20.2 ± 1.3%, respectively). Furthermore, the total cell number per day 8 blastocyst was significantly higher in the CICT group than in the SCNT group (176.2 ± 6.5 vs. 119.3 ± 7.7, p < 0.05). Moreover, CICT increased mitochondrial activity, as detected using MitoTracker Green. The mRNA levels of DNA methyltransferase 1 and DNA methyltransferase 3a were significantly lower (p < 0.05) in the CICT group than in the SCNT group. The mRNA level of DNA methyltransferase 3b was lower in the CICT group than in the SCNT group; however, this difference was not significant (p > 0.05). Taken together, these data suggest that CICT improves the in vitro developmental competence and quality of cloned bovine embryos.